Allende la libación: el Café - Sanabria, Carolina (2013)
This research deals with a short trip, whose departure is the disquisitions, theoretical at the beginning, that lead us to a simple grain. Since its origins, it’s been charged with fabulous versions; its trajectory swings in an originally remedial and simultaneously condemning application that though without being solved is transported to the legimate field of medical sciences. Its basic composition and the consuming habits that have made it an intellectual drink